Relationship between age at initiation of cysteamine treatment, adherence with therapy, and glomerular kidney function in infantile nephropathic cystinosis - Nießl, Christina; Boulesteix, Anne Laure; Oh, Jun; Palm, Katja; Schlingmann, Peter; Wygoda, Simone; Haffner, Dieter; Wühl, Elke; Tönshoff, Burkhard; Buescher, Anja; Billing, Heiko; Hoppe, Bernd; et al. (Molecular Genetics and Metabolism, 2022)
Infantile nephropathic cystinosis, due to impaired transport of cystine out of lysosomes, occurs with an incidence of 1 in 100–200,000 live births. It is characterized by renal Fanconi syndrome in the first year of life and glomerular dysfunction progression to end-stage kidney disease by approximately 10 years of age. Treatment with oral cysteamine therapy helps preserve glomerular function, but affected individuals eventually require kidney replacement therapy. This is because glomerular damage had already occurred by the time a child is diagnosed with cystinosis, typically in the second year of life. We performed a retrospective multicenter study to investigate the impact of initiating cysteamine treatment within the first 2 months of life in some infants and comparing two different levels of adherence in patients diagnosed at the typical age. We collected 3983 data points from 55 patients born between 1997 and 2020; 52 patients with 1592 data points could be further evaluated. These data were first analyzed by dividing the patient cohort into three groups: (i) standard treatment start with good adherence, (ii) standard treatment start with less good adherence, and (iii) early treatment start. At every age, mean estimated glomerular filtration rate (eGFR) was higher in early-treated patients than in later-treated patients. Second, a generalized additive mixed model (GAMM) was applied showing that patients with initiation of treatment before 2 months of age are expected to have a 34 ml/min/1.73 m2 higher eGFR than patients with later treatment start while controlling for adherence and patients' age. These data strongly suggest that oral cysteamine treatment initiated within 2 months of birth preserves kidney function in infantile nephropathic cystinosis and provide evidence of the utility of newborn screening for this disease.
CRIS-Team Scopus Importer:2022-07-22
Keywords: Cysteamine; Cystinosis; Glomerular function